Modos de aplicação de manganês e zinco em dois cultivares de soja - Souza, Marcelo Fernando Pereira [UNESP] (2015)
Research has been developed trying to identify the best management of the application of manganese and zinc for soybean; however, there is still no agreement on the results, because the dynamics of these nutrients in the soil is also influenced by the application method. The objective of this study was to verify in a clayey red Oxisol (Rhodic Hapludox) Cerrado phase, the influence of the application modes of Mn and Zn on nutritional characteristics (leaves, roots and grains), productive characteristics (production components and grain yield), biochemical (phytate, free amino acids and total protein) and physiological quality of two soybean cultivars. The study was conducted at the Federal Institute of Science and Technology of Mato Grosso - Campo Novo do Parecis, Brazil, in the years 2013/14 and 2014/15 growing season. The experimental design was a randomized block design, with four replications in a 2 X 10 factorial scheme. The treatments consisted of: two soybean cultivars (GMT 1179RR and 4182 GMT) and 10 differents application methods of Mn and Zn. The sources of Mn and Zn were Mn sulfate and Zn sulfate with recommendation of 5 kg ha-1 of the nutrient when applied to soil and 0.5% of the product solution, when applied to leaves as follow. T1: without application of Mn and Zn; T2: Mn soil application; T3: Zn soil application; T4: Mn foliar application; T5: Zn foliar application; T6: Mn soil application + Mn foliar application; T7: Zn soil application + Zn foliar application; T8: T2 + T3; T9: T4 + T5; T10: T6 + T7. We evaluated the concentrations of N, P, K, Ca, Mg, S, Mn, Zn, Fe and Cu in the leaves, root and grains, and the number of pods plant- 1, number of grains pod-1, number of plant-1 grain, grain mass plant-1, weight of 100 grains, grain yield, phytate content, free amino acids, protein and physiological quality of soybean seeds. Nutritional characteristics, yield components and grain yield, in addition to biochemical...